ANALISIS PEMAHAMAN KONSEP MATERI PECAHAN PADA SISWA KELAS 4 SD NEGERI 010091 KISARAN BARU - Sakila Azria Fitri; Nanda Aryanti Nasution; Cindy Syaharani; Anim Anim (Smart Education, 2025)
The concept of fractions has a fairly broad scope of implementation in everyday life. This study aims to understand the understanding of the concept of fractions in grade 4 students of SD Negeri 010091 Kisarang Baru. Fraction material is one of the basic mathematics topics that often causes difficulties for students, because it involves understanding parts of a whole. The objects in this study were grade 4 students of SD Negeri 010091 Kisaran Baru. The research method used in this study is a qualitative method with a descriptive approach in data analysis. with written test instruments, observations, and in-depth interviews with 26 grade 4 students. The purpose of this study is to help grade 4 students overcome difficulties in understanding the concept of fractions in mathematics learning. Through interactive learning, it is hoped that the mathematics learning process can be improved.Keywords: Fractions; Learning; Understanding; Mathematics; Concepts.